ANALISIS NILAI TAMBAH BAWANG GORENG PADA UD. SAFARI BAWANG GORENG DI KELURAHAN KEBUN TEBENG KOTA BENGKULU ; VALUE ADDED ANALYSIS ON FRIED ONION OF UD. SAFARI BAWANG GORENG IN KELURAHAN KEBUN TEBENG BENGKULU CITY - Zuhardi Perdana Putra; Reswita Reswita Reswita; Irnad Irnad Irnad (Jurnal Agroindustri, 2018)
ABSTRACTAgroindustry is an agriculture based industry that has an important role in economic growth in Indonesia. One of the agricultural subsector is horticultural crops, namely onion. The need for onion consumption in Indonesia has always increased. In the Bengkulu city there is a company engaged in the industry of fried onions are "UD. Safari Bawang Goreng". This research is done with consideration of the company has long standing, big enough company, and produce about 336 kg/day. Fried onions are processed products that are processed from the main source of raw material is onion. The processed onion comes from Brebes Java. To know the process can be done by the method of observation, and participation. Processed red onion products produce added value that can be analyzed by Hayami method. The process of onion processing into fried onions consists of several stages, namely the provision of raw materials, onion gaebage, sorting, slicing onion, affixing onion with flour, frying, pressing, packaging. The process of onion treatment into fried onions is called value added. The added value obtained in this study amounted to Rp 9549.65 / Kg BB.Keywords: Fried Onion, Hayami Method, Added Value.